Antioxidant Activity and Potential Bioactive Peptides from Skin Protein Hydrolysate of Yellowfin Tuna (Thunnus albacares) - Rachman, Sitti Hardiyanti; Santoso, Joko; Suseno, Sugeng Heri (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research Immersion of tuna skin using NaHCO3 at low temperatures effectively reduces the fat content. The DH value, MW, and amino acid composition are in line with the antioxidant activity of tuna skin hydrolysate. The ABTS method showed the highest antioxidant activity in tuna skin hydrolysate. FPH of tuna skin shows functional group characteristics and amino acid composition that are similar to collagen hydrolysate products. FPH of tuna skin has the potential as a source of antioxidants, ACE inhibitors, and antifibrinolytics. Abstract The tuna fillet industry produces abundant skin by-products with high protein, which has the potential as a raw material for fish protein hydrolysate (FPH) for a source of bioactive peptides. Exploration of bioactive peptides from fish skin is generally from hydrolyzed gelatin and collagen. The study aimed to produce FPH directly from tuna skin as an antioxidant and identify potential bioactive peptides. The research began by defatting using multiple concentrations of NaHCO3 and immersion times. The defatted fish skin was produced as FPH by enzymatic hydrolysis method using different papain enzyme concentrations and hydrolysis times. The selected treatments were assessed for antioxidant activity and bioactive peptides. The results showed that the defatting process using a 0.50% NaHCO3 for 30 minutes generated the highest reducing fat content in value was 80.53%. Using papain enzyme gave a significant effect on the DH of FPH, with value was 29.72-67.64%. Therefore, FPH obtained from different concentrations for 4 hours was chosen to characterize the antioxidant activity and bioactive peptide. Hydrolysis using 5% enzyme papain showed the highest antioxidant activity of DPPH, ABTS, and reducing power with values of 0.965 mg/mL, 0.495 mg/mL, and 0.415 absorbances, respectively. FPH possesses a molecular weight of 10.15-48.50 kDa. Functional groups detected were amides A, B, I, II, and III. Glycine, proline, and arginine became amino acids dominant of FPH. Based on the diversity of biopeptide compounds, several biological function candidates were detected, namely antioxidants, ACE inhibitors, and antifibrinolytics which have the potential to be used as nutraceutical products.